2017
DOI: 10.1016/j.vetimm.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microsomal prostaglandin E-synthase-1 (mPGES-1) selectively suppresses PGE 2 in an in vitro equine inflammation model

Abstract: Inhibition of prostaglandin E2 (PGE2) production effectively limits inflammation in horses, however nonspecific prostaglandin blockade via cyclooxygenase (COX) inhibition elicits deleterious gastrointestinal side effects in equine patients. Thus, more selective PGE2 targeting therapeutics are needed to treat inflammatory disease in horses. One potential target is microsomal prostaglandin E-synthase-1 (mPGES-1), which is the terminal enzyme downstream of COX-2 in the inducible PGE2 synthesis cascade. This enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Since Cox-2 inhibitors attenuate the production of all prostanoids, we feel confident that the use of a mPGES-1 inhibitor allows delineating the role of PGE 2 more specifically. While mPGES-1 inhibitors were reported to redirect the PGE 2 precursor PGH 2 to other prostanoids in vitro 26 , 43 , we did not observe such shunting in vivo, in line with other reports 44 , 45 . Epithelial CX3CL1 expression further corroborates previous reports, demonstrating that CX3CL1 is produced by peritoneal epithelial upon peritoneal dialysis, where it contributed to a fibrotic phenotype 27 , 46 .…”
Section: Discussionsupporting
confidence: 92%
“…Since Cox-2 inhibitors attenuate the production of all prostanoids, we feel confident that the use of a mPGES-1 inhibitor allows delineating the role of PGE 2 more specifically. While mPGES-1 inhibitors were reported to redirect the PGE 2 precursor PGH 2 to other prostanoids in vitro 26 , 43 , we did not observe such shunting in vivo, in line with other reports 44 , 45 . Epithelial CX3CL1 expression further corroborates previous reports, demonstrating that CX3CL1 is produced by peritoneal epithelial upon peritoneal dialysis, where it contributed to a fibrotic phenotype 27 , 46 .…”
Section: Discussionsupporting
confidence: 92%
“…Our PGE 2 values were consistent with those previously published for equine plasma (Martin & Jones, ) and synovial fluid (Frisbie, Al‐Sobayil, Billinghurst, Kawcak, & McIlwraith, ), as were our PL‐GAG (Calatroni, Avenoso, Ferlazzo, Lindner, & Campo, ) and SF‐GAG (Frisbie et al., ). While there was a significant relationship between BCS and FM and FP, the only outcome measures significantly correlated with inflammation biomarkers (i.e., PL‐PGE 2 ) were BCS, AL and BW.…”
Section: Discussionsupporting
confidence: 91%
“…In the veterinary literature, Kandefer‐Gola et al (2015) found that in canine mast cell carcinoma, a positive relationship between COX‐2 and mPGES1 exists and the authors suggested that mPGES1 inhibitors could be helpful in canine cancer treatment 68 . In an in vitro equine inflammation model, it was found that mPGES1 has an important role in inflammation and the authors indicated that mPGES1 inhibitors as a novel therapy in equine medicine are worthy of clinical trial 69 . Interestingly, mPGES1 Is not well studied in FOSCC, and even though we didn't see evidence for its expression being coupled to COX‐2 expression, it may still be an important driver of inflammation in the FOSCC microenvironment, and more investigations of feline mPGES1 as a potential therapeutic target are justified.…”
Section: Discussionmentioning
confidence: 99%